Serum IL-17 levels correlate with urinary albumin in systemic lupus erythematosus (SLE) pregnant mice model - Wahyuni, Sari; Pratiwi, Agustina Ida; Mawaddah, Sofia; Iswati, Retno Setyo (Universitas Gadjah Mada, 2023)
Women of reproductive age are more likely to have systemic lupus erythematosus (SLE), which frequently results in health issues, particularly during pregnancy. A normal pregnancy's first trimester shows a marked increase in the percentage of Th17 cells, which then steadily declined in the second and third trimesters. Meanwhile, IL-17 level increases in SLE-affected pregnant women. This study aimed to analyze the correlation between serum IL-17 and pregnancy outcome (fetus weight, blood pressure, urinary albumin) in SLE pregnant animal models. Twenty mice were randomly divided into two groups, including the normal pregnant group and SLE-pregnant group. The SLE pregnant mice was made by intraperitoneally induction of 0.5 mL pristane. Serum IL-17 was assayed by enzyme-linked immunosorbent assay (ELISA) method. The serum IL-17 level, the blood pressure and urinary albumin were significantly higher in the SLE pregnant mice group than those of the normal pregnant group (p< 0.05). The weight of fetus was significantly smaller in the group of SLE pregnant mice group than the normal pregnant group (p< 0.05). There was a significantly positive correlation between the serum IL-17 level and urinary albumin (p = 0.042; r = 0.459). In conclusion, serum IL-17 levels correlate with urine albumin in SLE pregnant models, but do not correlate with fetus weight and blood pressure.